A nitrogen-doped FeP material, a preparation method and application thereof
By introducing nitrogen atoms into the FeP lattice and optimizing the preparation process, nitrogen-doped FeP materials were prepared, solving the conductivity and stability problems of FeP materials in the electrochemical uranium removal process and achieving efficient and stable uranium removal effect.
Patent Information
- Application Number
- CN202610393220.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-27
- Publication Date
- 2026-06-23
Smart Images

Figure CN122254449A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of environmental functional materials and uranium-containing wastewater treatment technology, and particularly to a nitrogen-doped FeP material, its preparation method, and its application. Background Technology
[0002] Currently, the main methods for treating uranium-containing wastewater include chemical precipitation, adsorption, ion exchange, and membrane separation. However, all of these methods have significant technical limitations, making it difficult to simultaneously achieve treatment efficiency, controllability, and deep purification requirements. In contrast, electrochemical uranium removal, due to its mild reaction conditions, high removal efficiency, strong controllability, and low likelihood of generating secondary sludge, has become the preferred technological path for the deep treatment of uranium-containing wastewater. Its core lies in developing electrode materials that possess both excellent electronic conductivity and uranium reduction activity.
[0003] Among metal phosphides, FeP stands out as a research hotspot due to its wide availability of raw materials, low preparation cost, good environmental compatibility, and suitable redox potential, exhibiting excellent redox potential in electrochemical systems. However, pure FeP materials suffer from drawbacks such as low electronic conductivity, a limited number of surface electrochemical active sites, and insufficient stability of the crystal structure during electrochemical cycling. These drawbacks result in slow kinetics and limited adsorption capacity when used as electrode materials, and their activity easily decays during cycling, making it difficult to meet the application requirements of high-efficiency and stable electrode materials for electrochemical uranium removal. Summary of the Invention
[0004] One of the objectives of this invention is to provide a nitrogen-doped FeP material to improve the problems of low conductivity, few active sites, and poor cycling stability of traditional FeP-based materials.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] A nitrogen-doped FeP material, with FeP as the matrix and nitrogen atoms doped into the FeP lattice.
[0007] Furthermore, the nitrogen atoms exist in the FeP lattice in the form of substitutional doping.
[0008] Furthermore, the FeP has a pure-phase crystal structure.
[0009] Furthermore, the nitrogen-doped FeP material also includes a C component; apart from the C component, there are no other impurity phases.
[0010] Another object of the present invention is to provide a method for preparing nitrogen-doped FeP materials.
[0011] The preparation method includes the following steps:
[0012] (1) Provide iron-containing precursor, phosphorus-containing precursor and nitrogen-containing precursor, mix and dry to obtain precursor powder;
[0013] (2) The precursor powder is placed in an inert atmosphere and calcined at a preset temperature. After being kept at the temperature for a period of time, it is cooled to room temperature to obtain nitrogen-doped FeP material.
[0014] In the preparation process, the optimal precursor system and calcination process conditions (such as calcination temperature) can be determined in advance by screening the precursor system and calcination process.
[0015] Further, in step (1), a mixture of phosphorus-containing precursor and water (such as deionized water) is added (e.g., dropwise) to a mixed solid consisting of iron-containing precursor and nitrogen-containing precursor, and mixed evenly to form a precursor liquid phase mixture. After drying, precursor powder is obtained. Stirring is an optional operation to ensure uniform mixing; the stirring time is 30 min.
[0016] The drying temperature is 80℃, and the drying time is 24 hours. The drying process removes moisture and volatile impurities from the precursor.
[0017] After drying, the components can be ground. Grinding ensures that the components are fully contacted and fused, laying the foundation for subsequent uniform doping.
[0018] Furthermore, the mass ratio of the iron-containing precursor to the nitrogen-containing precursor is 1:1.
[0019] Furthermore, each 1g of iron-containing precursor and nitrogen-containing precursor corresponds to 4mL of water and 0.2mL of phosphorus-containing precursor. That is, the solid-liquid ratio is 10g:40ml:2ml (i.e., 1g:4mL:0.2mL) of mixed solid (iron-containing precursor + nitrogen-containing precursor):water:phosphorus-containing precursor (liquid).
[0020] Furthermore, the iron-containing precursor is ferrophthalocyanine, the phosphorus-containing precursor is phytic acid, and the nitrogen-containing precursor is dicyandiamide.
[0021] Both phthalocyanine iron and dicyandiamide contain carbon (C), and after calcination, C components can coexist in the product. The C components can improve the conductivity and specific surface area of the material, while also enhancing the structural stability of the product.
[0022] Furthermore, in step (2), the calcination temperature is 900℃; controlling the calcination temperature at 900℃ ensures that the product has a pure FeP crystal structure, contains C components in an amorphous form, and has no other impurity phases. The holding time is 6h to ensure that the reaction proceeds fully.
[0023] The heating rate during calcination is controlled at 10℃ / min to avoid excessively high local temperatures caused by rapid heating.
[0024] The inert atmosphere is argon, and the gas flow rate should not be too fast to prevent the product from being oxidized at high temperatures.
[0025] Furthermore, the nitrogen-doped FeP material can be applied to the uranium removal treatment of uranium-containing wastewater. Specifically, the uranium removal method includes the following steps:
[0026] The pH of uranium-containing wastewater was adjusted, and nitrogen-doped FeP material was added to the wastewater. The mixture was stirred and reacted at room temperature for a certain period of time to achieve uranium removal.
[0027] Furthermore, the pH value of the uranium-containing wastewater is adjusted to 3-11 (preferably pH=7).
[0028] The dosage of the nitrogen-doped FeP material is 0.1 g / L;
[0029] The stirring reaction was carried out over a period of 6 hours.
[0030] Furthermore, the initial concentration of uranium in the uranium-containing wastewater is 10 mg / L.
[0031] Furthermore, the stirring speed is 200 r / min.
[0032] The nitrogen-doped FeP material provided by this invention improves the uranium removal performance of FeP material by introducing nitrogen atoms into the FeP lattice, thereby optimizing the electronic structure and surface active sites of the material.
[0033] Thanks to the introduction of this nitrogen-doped structure, the material exhibits excellent performance indicators: in complex water bodies with pH=7 and high salt concentrations (e.g., nitrate nitrogen concentration below 7000 mg / L), the uranium removal equilibrium time is shortened to 6 h, the uranium removal rate can reach up to 100%, and the adsorption capacity can reach 4263.53 mg·g -1 More importantly, under these conditions, after 45 cycles of use, the uranium removal rate remained above 90%, and there was no significant material shedding.
[0034] The above results show that the nitrogen doping strategy provided by this scheme achieves stable embedding of nitrogen atoms in the FeP lattice, endowing the material with excellent adsorption capacity, fast kinetic response and long cycle stability, and has the potential for long service life and industrial application. Attached Figure Description
[0035] Figure 1 The image shows the XRD pattern of the nitrogen-doped FeP material prepared in this invention.
[0036] Figure 2Here is an HRTEM image of the nitrogen-doped FeP material prepared in this invention;
[0037] Figure 3 Aberration-corrected electron microscope image of the nitrogen-doped FeP material prepared in this invention;
[0038] Figure 4 Uranium removal rate curves of nitrogen-doped FeP materials prepared with precursors in different states; wherein the reaction time was 6 h and the initial uranium concentration was 10 mg / L;
[0039] Figure 5 The graphs show the uranium removal rates of nitrogen-doped FeP materials prepared at different calcination temperatures; the reaction time was 6 h and the initial uranium concentration was 10 mg / L.
[0040] Figure 6 The bar chart shows the cyclic uranium removal efficiency of nitrogen-doped FeP materials; the number of cycles was 45, and the initial uranium concentration was 10 mg / L. Detailed Implementation
[0041] To facilitate understanding by those skilled in the art, the present invention will be further described below with reference to embodiments. The content mentioned in the embodiments is not intended to limit the present invention. It should be noted in advance that the following embodiments were completed in a laboratory. Those skilled in the art should understand that the amounts of each component given in the embodiments only represent the ratio between the components, and are not specific limitations.
[0042] Nitrogen doping is an effective means of controlling the electronic structure of FeP and enhancing its surface activity. It can increase the number of active sites and accelerate the electron transfer rate by changing the charge distribution of the FeP lattice. However, existing nitrogen-doped FeP material preparation processes still have many shortcomings. On the one hand, the selection of precursor systems is relatively limited, lacking systematic screening of precursors in different states, resulting in insufficient precursor reactivity and difficulty in achieving uniform nitrogen doping. On the other hand, as a key parameter affecting the product phase and doping effect, the calcination temperature lacks targeted optimization in existing technologies, easily leading to a high number of impurity phases and uneven doping in the product. In addition, some existing methods also suffer from complex processes, high costs, and poor reproducibility, which seriously restricts their large-scale application.
[0043] Based on this, the present invention provides a nitrogen-doped FeP material and its preparation method. The present invention achieves uniform and stable nitrogen doping in the FeP lattice by systematically optimizing the precursor state and calcination temperature. The preparation process is controllable, solving the problems of numerous impurity phases and uneven doping in existing technologies. The obtained nitrogen-doped FeP material exhibits excellent uranium removal performance, providing important theoretical basis and engineering application value for the efficient and deep treatment of uranium-containing wastewater.
[0044] Specifically, the preparation method of this nitrogen-doped FeP material includes the following steps:
[0045] (1) Precursor screening and preparation: Iron-containing precursors, phosphorus-containing precursors and nitrogen-containing precursors were selected. By comparing the mixing uniformity of different physical states (liquid, foam, impurity phase) of precursor combinations and the purity of subsequent products, the optimal precursor system was screened.
[0046] Specifically, the iron-containing precursor was selected from ferrophthalocyanine, the phosphorus-containing precursor from phytic acid, and the nitrogen-containing precursor from dicyandiamide. The optimal precursor system obtained by screening was as follows: ferrophthalocyanine and dicyandiamide were mixed at a mass ratio of 1:1 to obtain a mixed solid, and then deionized water and phytic acid were added at a mass-volume ratio of 10 g: 40 mL: 2 mL (i.e., 1 g: 4 mL: 0.2 mL), and the mixture was stirred thoroughly (for 30 min) to form a liquid mixture.
[0047] The liquid precursor was dried at 80°C for 24 hours to completely remove moisture and volatile impurities, yielding precursor powder. Notably, the grinding step can be considered an optional operation to ensure sufficient contact between components; furthermore, phthalocyanine iron and dicyandiamide are rich in carbon, and subsequent calcination can form C components that coexist in the product, improving the material's conductivity, specific surface area, and structural stability.
[0048] (2) Screening and implementation of calcination process: The precursor powder obtained in step (1) is placed in a tube furnace under argon protection and heated at a heating rate of 10℃ / min. After holding at the temperature for 6 h, it is naturally cooled to room temperature to obtain nitrogen-doped FeP material.
[0049] Calcination temperature is a key parameter affecting the phase composition of the product. This step involved screening multiple temperature gradients (e.g., 500℃, 700℃, 800℃, 900℃) within the range of 500–900℃. Experiments showed that when the calcination temperature was below 900℃ (e.g., 500℃, 700℃, 800℃), the precursor thermal conversion was incomplete, resulting in unreacted precursor impurities or suboptimal crystallinity in the product. Only when the calcination temperature reached 900℃ did the precursor completely transform into a pure FeP crystal structure, accompanied by characteristic peaks of amorphous carbon, without the formation of other impurity phases. Therefore, 900℃ was determined to be the optimal calcination temperature. Furthermore, controlling the appropriate argon flow rate effectively prevented the product from being oxidized at high temperatures, ensuring a complete reaction and the integrity of the crystal structure.
[0050] (3) Characterization and verification: The structure and morphology of the product were characterized by XRD, HRTEM and aberration-corrected transmission electron microscopy to confirm the successful synthesis of the target product.
[0051] XRD analysis showed that the diffraction pattern of the product was consistent with the FeP standard card (PDF#78-1443), exhibiting only FeP characteristic peaks and amorphous peaks of C, with no other impurities. Furthermore, the FeP characteristic peaks showed a slight shift due to nitrogen doping, confirming the formation of a pure-phase FeP crystal structure, the coexistence of C components, and the successful incorporation of nitrogen. Further characterization using HRTEM and aberration-corrected electron microscopy not only revealed clear FeP lattice fringes, verifying good crystallinity, but also, using aberration-corrected electron microscopy for high-resolution imaging, revealed an ordered FeP lattice structure. Combined with elemental distribution and site occupancy analysis, this confirmed that nitrogen atoms were doped into the FeP lattice in the form of phosphorus sites.
[0052] (4) Uranium removal application method: The above nitrogen-doped FeP material is used for the treatment of uranium-containing wastewater. The specific operation steps are as follows:
[0053] The pH of the uranium-containing wastewater was adjusted to 3–11, with pH=7 being preferred. Nitrogen-doped FeP material was added to the pretreated uranium-containing wastewater at a dosage of 0.1 g / L. The reaction was carried out at room temperature (25±2℃) with stirring at 200 r / min for 6 h. After the reaction, the residual uranium content (residual uranium concentration) was determined by ultraviolet spectrophotometer. The test results showed that under these process conditions, the uranium removal efficiency of the material could reach up to 100%.
[0054] The nitrogen-doped FeP material prepared by the above method consists of a nitrogen-doped FeP matrix and a C component. Characterization results (XRD, HRTEM, and aberration-corrected transmission electron microscopy) confirmed that the FeP exhibits a pure-phase crystal structure, with nitrogen element embedded in the FeP lattice as a substitution dopant. The XRD pattern shows only characteristic FeP diffraction peaks and amorphous peaks of C, with no other impurity phases formed. This material achieves 100% uranium removal efficiency in uranium-containing (10 mg / L) wastewater, and the uranium removal efficiency remains above 90% after 45 cycles. Furthermore, it exhibits stable performance within the pH range of 3–11.
[0055] This method systematically screens precursor states (liquid, foam, and impurity phases) and calcination temperatures (500-900℃), identifying liquid precursors (liquid mixtures) and 900℃ as the optimal parameter combination to achieve uniform nitrogen doping in the FeP lattice. The resulting material not only features a simple and controllable preparation process, facilitating industrial scale-up, but also exhibits high uranium removal efficiency, strong stability, and excellent cycle performance, solving the problems of low uranium removal capacity, slow kinetics, and unclear preparation parameter control in existing FeP materials.
[0056] The following specific examples will provide further explanation.
[0057] In this embodiment, nitrogen-doped FeP materials were prepared according to the following steps:
[0058] (1) Precursor screening and preparation: Phthalocyanine iron (iron-containing precursor), phytic acid (phosphorus-containing precursor), and dicyandiamide (nitrogen-containing precursor) were provided. Different physical states (liquid, foam, and impurity phase) of the precursor combination after mixing and stirring were screened and compared. The optimal precursor preparation method was as follows: the selected precursors (phthalocyanine iron and dicyandiamide) were weighed at a mass ratio of 1:1, deionized water and phytic acid were added, and the solid-liquid ratio (mixed solid (phthalocyanine iron + dicyandiamide): deionized water: phytic acid) was 1g: 4mL: 0.2mL. The mixture was stirred for 30min to mix evenly, and then dried at 80℃ for 24h to obtain precursor powder.
[0059] (2) Screening and implementation of calcination process: The above precursor powder was placed in a tube furnace, and argon gas was introduced as a protective atmosphere. Calcination experiments were carried out at 500℃, 700℃, 800℃, and 900℃ respectively, with a heating rate of 10℃ / min. After holding at the temperature for 6 hours, the mixture was naturally cooled to room temperature to obtain the target material. XRD characterization revealed that the FeP characteristic diffraction peaks in the product obtained at 900℃ were consistent with the FeP standard card (PDF#78-1443), and an amorphous peak of C was also present. There were no other impurity phases, and the FeP characteristic peaks showed a slight shift, indicating that nitrogen atoms successfully entered the FeP lattice, causing lattice distortion (i.e., nitrogen doping). At 500℃, the product contained unreacted impurity phases, and the FeP crystalline phase had not yet formed. At 700℃ and 800℃, although the precursor had decomposed (an amorphous peak of C appeared), it had not completely transformed into the FeP crystalline phase. Therefore, the optimal calcination temperature was determined to be 900℃, and the target material (nitrogen-doped FeP material) was prepared according to this temperature.
[0060] (3) Characterization and verification: The product obtained by calcination at 900℃ was characterized by XRD, HRTEM and aberration electron microscopy, see [reference]. Figure 1-3 .like Figure 1 As shown, the XRD pattern indicates that the characteristic diffraction peaks of FeP in the product are consistent with those of the FeP standard card (PDF#78-1443), and an amorphous peak of C is also present. No other impurity phase peaks are observed, and the crystal plane diffraction peaks of FeP show a slight shift, confirming successful nitrogen doping and the resulting lattice distortion, with the coexistence of C components. Figure 2 As shown, the HRTEM image reveals that the product has clear FeP lattice fringes with a lattice spacing of 0.22 nm, corresponding to the (111) crystal plane of FeP, indicating good crystallinity; Figure 3 As shown, the aberration-corrected electron microscopy image clearly shows the FeP lattice, in which Fe atoms (purple spheres) are distributed in an orderly manner as metal active centers in the lattice, P atoms (orange spheres) form typical Fe-P coordination bonds with Fe atoms, constituting the core framework of the FeP matrix; N atoms (blue spheres) are introduced into the FeP lattice system in the form of doping (substitution doping), further confirming the doping modification of FeP by N, forming an N-FeP active phase.
[0061] This embodiment compared and tested the effects of precursors in different states on the uranium removal performance of the material (reaction conditions: room temperature, reaction time 6 h, initial uranium concentration 10 mg / L; specific uranium removal methods are described in this article; material preparation methods are the same as above), and the results are shown in [link to relevant documentation]. Figure 4 .from Figure 4 As can be seen, when the precursor system is liquid, the final sample material has a significantly higher uranium removal rate than the comparative samples prepared with foamy and impurity precursor systems. Therefore, the optimal precursor system is a liquid mixture.
[0062] This embodiment compared and tested the effect of different calcination temperatures on the uranium removal performance of the material (reaction conditions: room temperature, reaction time 6 h, initial uranium concentration 10 mg / L; specific uranium removal methods are described in this article; material preparation methods are the same as above), and the results are shown in [link to relevant documentation]. Figure 5 .from Figure 5 As can be seen, the sample prepared at 900℃ (denoted as N-FeP@C-900) exhibits the best uranium removal rate, and its performance is significantly better than the comparative samples prepared at 500℃, 700℃, and 800℃ (denoted as Fe-P / N@C-500, Fe-P / N@C-700, and Fe-P / N@C-800, respectively). Therefore, 900℃ is the optimal calcination temperature for preparing nitrogen-doped FeP materials.
[0063] This embodiment also conducted a uranium removal application verification experiment on the prepared nitrogen-doped FeP material (N-FeP@C-900).
[0064] Wastewater preparation: Simulated uranium-containing wastewater with a uranium concentration of 10 mg / L (nitrate concentration of 0.5 M) was prepared, and the pH was adjusted to 7. 0.1 g / L of nitrogen-doped FeP material was added (under optimal preparation conditions: liquid precursor + calcination at 900℃). The reaction was carried out at room temperature (25±2℃) with stirring at 200 r / min for 6 h. After the reaction, the residual uranium content was determined by ultraviolet spectrophotometry. Test results showed that the uranium removal efficiency of the material could reach up to 100%. Figure 6 As shown, after 45 cycles, the uranium removal rate of the material remains above 90%; it exhibits stable performance under complex conditions of pH=7 and salt concentration (nitrate concentration (calculated as nitrate nitrogen)) <7000 mg / L, with an adsorption capacity reaching 4263.53 mg·g. -1 Furthermore, the material does not show obvious shedding or dissolution and has a long service life.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] 1. Precursor system optimization to ensure doping uniformity: By systematically screening precursor combinations in different states, the optimal precursor system was determined, which effectively improved the reactivity and mixing uniformity of the precursors, ensuring uniform doping of nitrogen and uniform coexistence of C components; at the same time, by optimizing the precursor ratio, the purity of FeP and the reasonable distribution of C components in the product were further ensured.
[0067] 2. Precise control of the calcination process to achieve pure-phase synthesis: A systematic gradient screening of calcination temperature was conducted, and 900℃ was determined to be the optimal process parameter. This condition avoids the problems of incomplete reaction due to excessively low temperature or product deterioration due to excessively high temperature, and successfully prepares pure-phase nitrogen-doped FeP materials.
[0068] 3. Simple process and low cost, with potential for large-scale production: The preparation method of this invention is simple, controllable, and reproducible; the required raw materials are widely available and inexpensive, making it easy to achieve large-scale production; the obtained material has a unique crystal structure and excellent performance, showing broad application prospects in fields such as electrocatalysis, energy storage, and environmental remediation.
[0069] 4. Excellent uranium removal performance: Nitrogen substitution doping can significantly regulate the electronic structure of FeP and increase the number of surface active sites. Experiments show that the adsorption equilibrium time for uranium by this material is shortened to 6 h, and the uranium removal rate can reach up to 100%, solving the problem of low uranium removal efficiency of traditional electrocatalytic materials.
[0070] 5. Excellent stability and recyclability: After 45 cycles, the uranium removal rate remains above 90%; it maintains stable performance under complex water quality conditions such as pH=7 and high salinity (nitrate nitrogen concentration <7000 mg / L), with an adsorption capacity of up to 4263.53 mg·g. -1 Furthermore, the material does not detach significantly and has a long service life.
[0071] The embodiments described above are merely preferred embodiments of the present invention and are not exhaustive examples of all possible implementations of the present invention. Any obvious modifications made by those skilled in the art without departing from the principles and spirit of the present invention should be considered to be included within the scope of protection of the claims of the present invention.
Claims
1. A nitrogen-doped FeP material, characterized in that, Using FeP as the matrix, nitrogen atoms are doped into the FeP lattice.
2. The method for preparing the nitrogen-doped FeP material according to claim 1, characterized in that, Includes the following steps: (1) Provide iron-containing precursor, phosphorus-containing precursor and nitrogen-containing precursor, mix and dry to obtain precursor powder; (2) The precursor powder is placed in an inert atmosphere and calcined at a preset temperature. After being kept at the temperature for a period of time, it is cooled to room temperature to obtain nitrogen-doped FeP material.
3. The preparation method according to claim 2, characterized in that, In step (1), a mixture of phosphorus-containing precursor and water is added to a mixture of iron-containing precursor and nitrogen-containing precursor to form a precursor liquid phase mixture, which is then dried to obtain precursor powder.
4. The preparation method according to claim 3, characterized in that, The mass ratio of the iron-containing precursor to the nitrogen-containing precursor is 1:
1.
5. The preparation method according to claim 4, characterized in that, Each 1g of iron-containing precursor and nitrogen-containing precursor corresponds to 4mL of water and 0.2mL of phosphorus-containing precursor.
6. The preparation method according to any one of claims 2-5, characterized in that, The iron-containing precursor is ferrophthalocyanine, the phosphorus-containing precursor is phytic acid, and the nitrogen-containing precursor is dicyandiamide.
7. The preparation method according to claim 2, characterized in that, In step (2), the calcination temperature is 900℃ and the holding time is 6h.
8. The application of the nitrogen-doped FeP material according to claim 1 in the removal of uranium from uranium-containing wastewater.
9. The application according to claim 8, characterized in that, Includes the following steps: The pH of uranium-containing wastewater was adjusted, and nitrogen-doped FeP material was added to the wastewater. The mixture was stirred and reacted at room temperature to remove uranium.
10. The application according to claim 9, characterized in that, The pH value of the uranium-containing wastewater was adjusted to 3-11; The dosage of the nitrogen-doped FeP material is 0.1 g / L; The stirring reaction was carried out over a period of 6 hours.
